2018
DOI: 10.17584/rcch.2018v12i1.7059
|View full text |Cite
|
Sign up to set email alerts
|

Efecto de la colchicina sobre la morfología foliar y los estomas de <i>Kalanchoe daigremontiana</i> Raym.-Hamet & H.Perrier (Crassulaceae)

Abstract: El presente estudio evaluó el efecto de diferentes concentraciones y tiempo de exposición de colchicina, sobre la morfología foliar y los estomas de Kalanchoe daigremontiana. Inicialmente, se recolectaron y se sometieron las plántulas de K. daigremontiana a concentraciones de 0,025% y 0,1% (p/v) de colchicina y a dos tiempos de exposición (24 y 48 horas). Posteriormente, se realizaron estudios morfológicos como la altura de la planta (AP), anchura de la hoja (AH), número de hojas (NH), longitud foliar (LH), es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 23 publications
2
6
0
Order By: Relevance
“…On the other hand, height, leaves number, foliar thickness, foliar volume and num ber of seedlings with the rest of treatments (Fig. 2), the direct effect that colchicine has on the morphology could be confirmed (Salazar et al 2018); in that way, the useof 0.15%for48h,0.1%and0.15%for72hcauseda con si derableincreaseinfoliarthicknessand91.7,78.7and 100 % (respectively) of tetraploid cells in Aloe vera (Molero et al 2018). Similarly, 3 species of kumquats submitted to colchicine produced thicker, significantly rounder and heavierleaves(Nukayaetal.2019).Next,whencomparing the use of 0.05 % and 0.025 % for 24 h (T2 and T3), likewise, the use of 0.1 % and 0.05 % for 48 h (T5 and T6), it is observed that even doubling the colchicine con cen tra tionitdoesnotachieveasignificantdifferencebetween most of the variables of these treatments, which is similar toGalloneetal.…”
Section: Discussion Morphological Studymentioning
confidence: 85%
See 4 more Smart Citations
“…On the other hand, height, leaves number, foliar thickness, foliar volume and num ber of seedlings with the rest of treatments (Fig. 2), the direct effect that colchicine has on the morphology could be confirmed (Salazar et al 2018); in that way, the useof 0.15%for48h,0.1%and0.15%for72hcauseda con si derableincreaseinfoliarthicknessand91.7,78.7and 100 % (respectively) of tetraploid cells in Aloe vera (Molero et al 2018). Similarly, 3 species of kumquats submitted to colchicine produced thicker, significantly rounder and heavierleaves(Nukayaetal.2019).Next,whencomparing the use of 0.05 % and 0.025 % for 24 h (T2 and T3), likewise, the use of 0.1 % and 0.05 % for 48 h (T5 and T6), it is observed that even doubling the colchicine con cen tra tionitdoesnotachieveasignificantdifferencebetween most of the variables of these treatments, which is similar toGalloneetal.…”
Section: Discussion Morphological Studymentioning
confidence: 85%
“…The genus Kalanchoe belongs to the Crassulaceae family which includes about 125 described species (Salazar et al 2018). Fifty six species are native to Southern and Eas tern Africawhiletheremaining60speciesarenativetoMa da gas car (Pokhrel & Karsai 2015, Vlielander et al 2018.…”
Section: Impact Of Colchicine On Leaf Morphology and Stomatics Of Kalanchoe Tubiflora (Harv) Raym-hamet (Crassulaceae)mentioning
confidence: 99%
See 3 more Smart Citations